Abatacept in the treatment of severe, longstanding, and refractory uveitis associated with juvenile idiopathic arthritis - Tappeiner, Christoph; Miserocchi, Elisabetta; Bodaghi, Bahram; Kotaniemi, Kaisu; Mackensen, Friederike; Gerloni, Valeria; Quartier, Pierre; Lutz, Thomas; Heiligenhaus, Arnd (The journal of rheumatology, 2015)
Objective. Abatacept (ABA), a selective T cell costimulation modulator that binds to CD80 and CD86 on antigen-presenting cells, was investigated for its antiinflammatory effect in treating severe chronic uveitis associated with juvenile idiopathic arthritis (JIA). - Methods. Our retrospective study was conducted by members of the Multinational Interdisciplinary Working Group for Uveitis in Childhood (MIWGUC). Patients with JIA who are receiving ABA treatment for active uveitis were included. In all patients, uveitis had been refractory to previous topical and systemic corticosteroids, immunosuppressives, and at least 1 tumor necrosis factor-α inhibitor. A standardized protocol was used to document uveitis (MIWGUC) and arthritis. Baseline visit and visits at 3, 6, 9, and 12 months before and after ABA start were evaluated. Primary outcome measure was defined as achievement of uveitis inactivity; secondary outcome measures were tapering of corticosteroid and/or immunosuppressive treatment, and occurrence of complications. - Results. In all, 21 patients (16 female) with active uveitis (n = 21) and arthritis (n = 18) were included (mean age 11.8 ± 3.6 yrs). In 7 of 18 patients with active arthritis at baseline, inactivity was achieved following ABA treatment. Uveitis inactivity was achieved in 11 patients, but recurred later in 8 of them, and remained active in another 10 cases. Systemic corticosteroids or immunosuppression were tapered in 3 patients, but uveitis recurred in all of them during further followup. Ocular complications secondary to uveitis were present in 17 patients at baseline, while 3 patients developed new ocular complications during followup. - Conclusion. A sustained response to ABA was uncommon in patients with severe and refractory uveitis.
Gesehen am 29.06.2020